The thromboelastogram is confounded by hematocrit in clinical samples tested on both mechanical and acoustic platforms - Hess, Aaron S. (Frontiers in Medicine, 2024)
Red blood cells are critical participants in normal hemostasis, but in vitro experiments have shown that the thromboelastogram (TEG) maximum amplitude has a paradoxical inverse relationship with hematocrit. This study reviewed all samples at a single academic institution where any mechanical (TEG 5000) or acoustic (TEG 6s) TEG was drawn within 5 min of hematocrit measurement. A total of 7,176 samples were identified using complete TEG and conventional coagulation test data (6,384 mechanical, 744 acoustic, and 48 both). In the primary analysis, hematocrit was negatively associated with the maximum amplitude on both mechanical and acoustic platforms after adjusting for relevant confounders. This suggests that the thromboelastogram may misrepresent the contribution of red blood cells in normal hemostasis.